2021
DOI: 10.1016/j.omtn.2021.03.018
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs associated with glioblastoma: From transcriptional noise to novel regulators with a promising role in therapeutics

Abstract: Glioblastoma multiforme (GBM) is the most widespread and aggressive subtype of glioma in adult patients. Numerous long non-coding RNAs (lncRNAs) are deregulated or differentially expressed in GBM. These lncRNAs possess unique regulatory functions in GBM cells, ranging from high invasion/ migration to recurrence. This review outlines the present status of specific involvement of lncRNAs in GBM pathogenesis, with a focus on their association with key molecular and cellular regulatory mechanisms. Also, we highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 117 publications
1
25
0
Order By: Relevance
“…The recent researches on lncRNAs have reported that intergenic non-coding RNA can act as endogenous miRNA sponge in cancer cells to promote tumor development. 27 Hence molecular classi cation based on expression of lncRNAs may direct for gene therapy and may aid to a better procedure for targeted therapy selection. 28,29 In the current prospective study, two lncRNAs were investigated (lncRNA565 and lncRNA641) in blood samples from GBM patients and a healthy control group were recruited.…”
Section: Discussionmentioning
confidence: 99%
“…The recent researches on lncRNAs have reported that intergenic non-coding RNA can act as endogenous miRNA sponge in cancer cells to promote tumor development. 27 Hence molecular classi cation based on expression of lncRNAs may direct for gene therapy and may aid to a better procedure for targeted therapy selection. 28,29 In the current prospective study, two lncRNAs were investigated (lncRNA565 and lncRNA641) in blood samples from GBM patients and a healthy control group were recruited.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs were initially described as mere "transcriptional noise", but now increasing studies have demonstrated that LncRNAs act as critical modulators in a variety of physiological activities [29]. However, only a relatively limited number of LncRNAs have been confirmed to have critical biological functions, and molecular mechanisms of most LncRNAs have not been illustrated [30].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs interact with proteins or other non-coding RNAs to regulate gene expression in cis and trans to modulate cancer phenotypes (10,14). Several differentially expressed lncRNAs have been identified in GBM, which regulate various aspects of GBM pathology (15)(16)(17)(18)(19)(20). TGF-b-regulated lncRNAs modulate invasion, metastasis, and EMT in various cancers (21).…”
Section: Introductionmentioning
confidence: 99%